Women’s Language Features Used by the Character in Encanto Movie - ni made, dela pradnyani (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 1 (2024): Maret, 2024)
This study examines the distinctions between men and women when speaking, identifies women's language features based on Lakoff’s women’s language features theory (1975), and the dominating features employed by the character. Women speak more politely to avoid overstepping the addressees' rights. Therefore, women are well-known as more powerless than men because women also apply the terms of avoidance of swearing strong words in their statements. Thus, the researcher analyzed Encanto movie that analyzed women’s language features used by Encanto ’s women characters. The researcher chose the Encanto movie because women mostly play in this movie. This movie also shows some expressions that indicate the language used by women and men in society differently. The research was qualitative, primarily descriptive research. The study uses the Encanto movie as the primary data and the movie’s script as secondary data to complement the analysis. While collecting data, the researcher watched the movie several times, read the script carefully, and noted the women's utterances in the movie. Through the analysis, the researcher did, found 2 lexical hedges (15,4%), 2 tag questions (15,4%), 2 rising intonation (15,4%), 2 intensifiers (15,4%), 2 ‘hypercorrect grammar’ (15,4%), 1 avoidance of swear strong words (7,6%), and 2 emphatic stress (15,4%). The last are ‘empty’ adjectives, ‘super’ polite forms, and precise color terms that have no case (0%). In general, the features stated by Lakoff have a balanced use in this movie.